(untitled) (Dhaka University Journal of Linguistics, 2011)
The means of communication among the workers of the tea estates in greater Sylhet, locally called ’Deshoali’ Bhasha, has a lexicon that contains, among others, words of Hindi and Bengali origin. The present article includes some unfinished reflections on some aspects of the lexicon of this dialect and phonological analysis of ’Deshoali’ Bhasha. Key words: Deshoali bhasha; aspect; analyzed; phonology; paradigms. DOI: 10.3329/dujl.v2i4.6906 Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.173-184